Spatio-Temporal Differentiation of Cancer Incidence in Slovakia - Vilinová, Katarína; Repaská, Gabriela; Vojtek, Matej; Dubcová, Alena (European Spatial Research and Policy, 2018)
Coping with the prevention, diagnosis and therapy of cancers is a challenging medical task with continuing consequences for the development of population health status and economy of health in each country. The occurrence of cancers shows an upward trend in the world. A comprehensive fight against cancers should involve the spatial aspect which is best applied in the field of medical geography. The key indicators for the surveillance of cancers include mortality and incidence, but also prevalence. Incidence plays a more and more important role in the period of an increase in cancers. In the investigation of this issue specific analytical methods were used, such as spatial autocorrelation. Standardized cancer incidence in Slovakia was analyzed in the case of men and women. The years 1997, 2009 and the period 1997–2009 were chosen to compare the incidence. The results of partial analyses show the situation in districts of Slovakia from the perspective of incidence development and its spatial differentiation.